قراءة سيميائية فى رواية راس المحنة لعز الدين جلاوجى : مقاربة فى المكون السردى - الوافي، سامي Alwafi, Sami (جامعة الجلفة, 2017)
تناولنا في مقالنا هذا بالدراسة والتحليل المكون السردي في رواية "راس المحنة" للروائي الجزائري عز الدين جلاوجي وفق الآليات التي أقرها غريماس، محاولين معها الأخذ بعين الاعتبار جملة ملفوظات الحالة والتحول التي ميزت شخوصها، من خلال ربط الأدوار التي أدتها أثناء إجراء عمليات التحويل بالبرامج السردية فيها، لما أظهرته لنا منذ البداية من انقسام في المواقف بين رؤيتين لنوعين من العلاقات، نشأت بين طرفين متضادين هنا هما: السلطة/ المجتمع = المثقف، من أجل تحقيق موضوع القيمة.
In the present article we dealt with the study and analysis of the narrative component in the novel "Rass El- mihna" of the Algerian novelist "Azze- dine Djelaoudji" according to the mechanisms approved by Grimas ; trying to take into account the state utterences as well as the doing utterences which characterized its characters by connecting the roles which they have performed during the conversion processes with the narrative programs within it ; through what it Shows us from the beginning about the split of its characters between two visions to two types of relation between them, and that will be established between two opposite parties: The authority/ the society = the intellectual, for the Subject value.
Keywords: رواية رأس المحنة -- جلاوجى، عز الدين -- النقد الأدبى -- السرد الأدبى